EFFETS HYPOGLYCEMIQUE ET ANTI-HYPERGLYCEMIQUE DE L’EXTRAIT ETHANOLIQUE 70 % DE RACINES DE RAUVOLFIA VOMITORIA AFZEL (APOCYNACEAE) - Leatitia Akouah Richmonde N’doua; Kouakou Jean Claude Abo; Serge Aoussi; Moussa Gbogbo; Angoue Paul Yapo; Etienne Ehouan Ehile (European Scientific Journal, ESJ, 2015)
Rauwolfia vomitoria Afzel. (Apocynaceae) is a plant used in traditional medicine in the Ivory Coast for the treatment of several illnesses such as malaria, diarrhea, rheumatism, high blood pressure, and diabetes. This study aims to determine the level of toxicity of a 70 % ethanol extract of the root of that plant (HARv) and to evaluate its hypoglycemic and anti-hyperglicemic activities. It occurs that HARv shows no toxicity when administered orally to rats up to a concentration of 5000 mg/kg of body weight. However, doses of 500, 700 and 1000 mg/kg of body weight lead to hypoglycemia when HARv is administered via the oral route. Similar to the effect of glibenclamide (in a concentration of 10 mg/kg of body weight), concentrations of 700 and 1000 mg/kg of body weight of HARv significantly reduce hyperglycemia induced by the administration of 4 g/kg of body weight of glucose. The presence of saponins, flavonoids, and tannoids in the extract may cause the observed hypoglycemic and anti-hyperglycemic effects. We infer from this study that 70 % ethanol extract of the roots of Rauwolfia vomitoria is not toxic when administered orally to rats. In addition, HARv shows hypoglycemic and anti-hyperglycemic effects, explaining its use in traditional medicine for the treatment of diabetes.